Rigidity, Discretion, and the Costs of Writing Contracts - Battigalli, Pierpaolo; Maggi, Giovanni (American Economic Review, 2002)
In this paper we model contract incompleteness “from the ground up,” as arising endogenously from the costs of describing the environment and the parties' behavior. Optimal contracts may exhibit two forms of incompleteness: discretion, meaning that the contract does not specify the parties' behavior with sufficient detail; and rigidity, meaning that the parties' obligations are not sufficiently contingent on the external state. The model sheds light on the determinants of rigidity and discretion in contracts, and yields rich predictions regarding the impact of changes in the exogenous parameters on the degree and form of contract incompleteness.